2016
DOI: 10.1002/mds.26835
|View full text |Cite
|
Sign up to set email alerts
|

Individual changes in preclinical spinocerebellar ataxia identified via increased motor complexity

Abstract: Our results provide evidence for subclinical motor changes in spinocerebellar ataxia, which allow to discriminate patients without clinical signs even on a single-subject basis and may help capture disease progression in the preclinical phase. © 2016 International Parkinson and Movement Disorder Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 40 publications
5
63
0
1
Order By: Relevance
“…We have shown that precise spatiotemporal calibration in combination with a two-sided setup of sensors provides better statistical agreement with a gold standard motion capturing system than previously reported systems [1,2]. The excellent agreement with the VICON system suggests that, in addition to differences between patients and healthy controls, even subtle changes in gait, such as in preclinical cerebellar ataxia [36], might be detectable. Furthermore, the low-costs make multi-center studies involving clinical centers without dedicated motion laboratories feasible, allowing for distributed investigation of rare movement disorders.…”
Section: Discussionmentioning
confidence: 78%
“…We have shown that precise spatiotemporal calibration in combination with a two-sided setup of sensors provides better statistical agreement with a gold standard motion capturing system than previously reported systems [1,2]. The excellent agreement with the VICON system suggests that, in addition to differences between patients and healthy controls, even subtle changes in gait, such as in preclinical cerebellar ataxia [36], might be detectable. Furthermore, the low-costs make multi-center studies involving clinical centers without dedicated motion laboratories feasible, allowing for distributed investigation of rare movement disorders.…”
Section: Discussionmentioning
confidence: 78%
“…The definition of the prodromal stage in SCA2 comes from follow‐up and cross‐sectional studies carried out during the past 2 decades in the Cuban and European population of SCA2 preclinical individuals . These studies have included clinical somatic and autonomic assessments of the nervous system, semiquantitative rating of ataxia using clinical scales, neuropsychological studies, and imaging investigations.…”
Section: Criteria Defining the Prodromal Stage In Sca2 Preclinical Camentioning
confidence: 99%
“…Electrophysiological and quantitative neurological tests have become helpful approaches to characterize the SCA2 prodromal stage, providing several functional biomarkers with high diagnostic and predictive value and close association with the mutation size (Table ).…”
Section: Functional Criteriamentioning
confidence: 99%
“…It has been shown in laboratory-based assessments that measures of spatial and temporal movement variability allow distinctively to capture and characterize the specificities of ataxic gait [3][4][5][6][7][8][9][10] . Moreover, they allow to quantify disease severity even at preclinical stages of DCA 11,12 and to capture treatment-induced improvements in a fine-grained fashion [13][14][15] , thus suggesting a high potential as both progression and treatment response parameters in the upcoming treatment trials [16][17][18] . Recently, first studies showed that such measures of spatio-temporal variability characterizing ataxic gait can also be captured using wearable inertial sensors in clinical assessments 19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…Variability measures were calculated using the coefficient of variation CV=σ/μ, normalizing the standard deviation with the mean value 34 . On this basis, stride length CV (StrideL CV ) and stride time CV (StrideT CV ) were determined, which have shown to be sensitive to ataxia severity in constrained lab-based walking 3,5,7,11,12 .…”
Section: Discussionmentioning
confidence: 99%